Timing of antiretroviral therapy for HIV-infected patients with cytomegalovirus retinitis: study protocol of a multi-center prospective randomized controlled trial - He, Xiao-Qing; Huang, Yin-Qiu; Zeng, Yan-Ming; Qin, Yuan-Yuan; Tang, Sheng-Quan; Xu, Xiao-Lei; Harypursat, Vijay; Lu, Yan-Qiu; Liu, Min; Yuan, Jing; Chen, Yao-Kai (Current controlled trials in cardiovascular medicine, 2021)
Cytomegalovirus retinitis (CMVR) is an important opportunistic infection (OI) occurring mainly in patients with acquired immunodeficiency syndrome (AIDS) and has the potential to cause severe visual impairment and blindness among AIDS patients. Subsequent to the adoption and implementation of widespread antiretroviral therapy (ART), the prognosis of AIDS-associated CMVR has been substantially improved. Nevertheless, the equivocal clinical evidence as regards the optimal timing for ART initiation in patients with an established CMVR diagnosis is required. We therefore designed the present study in order to investigate the optimal timing for ART initiation in AIDS/CMVR patients. This will be a prospective, randomized controlled trial to be performed at 17 hospitals in mainland China. A total of 300 participants with CMVR will be randomly assigned to an early ART initiation group (ART initiation within 2 weeks after anti-CMV therapy), or a deferred ART initiation group (initiation of ART more than 2 weeks after anti-CMV therapy) at a 1:1 ratio. All participants will receive 48 weeks of follow-up after anti-CMV therapy initiation. Our primary outcome will be the incidence of visual loss (to a visual acuity worse than 20/40 or 20/200) in the two groups during the 48-week follow-up period. Secondary outcomes will include changes in HIV virological suppression and serum CD4 T-cell counts, the incidence of mortality, retinitis progression (movement of the peripheral border of a CMV lesion ≥ ½ disc diameter, or occurrence of a new CMV lesion), retinal detachment, immune recovery uveitis (IRU), and other OIs and adverse events between the two study groups during the 48 weeks of follow-up. The study aims to investigate the optimal timing for ART initiation in AIDS/CMVR patients. We hope to be able to extract robust clinical evidence for use in optimal AIDS/CMVR management should our trial be successful. This research was registered as one of the twelve clinical trials under the name of a general project "A study for precision diagnosing and treatment strategies in difficult-to-treat AIDS cases and HIV-infected patients with highly fatal or highly disabling opportunistic infections", ChiCTR1900021195. Registered on 1 February 2019, http://www.chictr.org.cn/showproj.aspx?proj=35362 .